Factors associated with fear of COVID-19 prior to returning to in-person classes at a Peruvian medical school - Dextre-Vilchez, Sergio Armando (2023)
Objective: To identify the factors associated with fear of COVID-19 prior to returning to in-person classes among medicalstudents. Materials and methods: An observational, analytical and cross-sectional study. Through convenience sampling, aquestionnaire was administered to 252 students from a medical school in Huancayo, Peru. The questionnaire consisted of a first section comprising the study information and informed consent, another one devoted to the sociodemographic characteristics and a last section which included validated questionnaires used in similar contexts, such as the Fear of COVID-19 Scale (FCV-19S), and a psychological questionnaire, i.e., the DASS-21 questionnaire, made up of three subscalesthat assess both the presence and level of depression, anxiety and stress. To determine the correlation between thescales, the Pearson correlation coefficient was used. In addition, crude and adjusted prevalence rates were calculatedusing generalized linear models. The significance was defined as a p value < 0.05. Results: The average fear of COVID-19 score was 14.99 ± 6.32 points and 26.98 % of the students showed a high level offear. The prevalence of depression, anxiety and stress was 30.95 %, 31.75 % and 28.57 %, respectively. The results of thecrude regression analysis indicated that the factors associated with high fear were complete vaccination (cPR: 0.64), depression (cPR: 1.76), anxiety (cPR: 2.42) and stress (cPR: 2.22). Moreover, the results of the adjusted regression analysisrevealed that complete vaccination (cPR: 0.65), trust in university policies and guidelines (aPR: 0.50), trust in governmentpolicies (aPR: 1.76) and anxiety (aPR: 2.18) were factors associated with high fear.Conclusions: These results suggest that each educational institution should adopt measures and strategies to provide safeplaces that reduce the spread of COVID-19 and enable the development of an optimal educational environment.